2020
DOI: 10.3390/jpm10040218
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PET–MRI Imaging in Paediatric and TYA Brain Tumours: Clinical Applications and Challenges

Abstract: (1) Background: Standard magnetic resonance imaging (MRI) remains the gold standard for brain tumour imaging in paediatric and teenage and young adult (TYA) patients. Combining positron emission tomography (PET) with MRI offers an opportunity to improve diagnostic accuracy. (2) Method: Our single-centre experience of 18F-fluorocholine (FCho) and 18fluoro-L-phenylalanine (FDOPA) PET–MRI in paediatric/TYA neuro-oncology patients is presented. (3) Results: Hybrid PET–MRI shows promise in the evaluation of gliomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…MRI is used before treatment and at the end of treatment or disease progression [295,296] and to assess neurological complications of cancer treatment [297]. PET/MRI is used in brain tumor grading and staging [298,299] as a diagnostic and therapeutic strategy for glioma [300] and for improved diagnostic and therapeutic assessment in pediatric, teenage, and young adult brain tumors [301]. 11 C-methyl-L-methionine (C-11-MET) PET/MRI was found to improve the diagnostic accuracy to differentiate treatment-related changes from true progression in recurrent glioma [302] and was useful for the assessment of isocitrate dehydrogenase (IDH) status [303].…”
Section: Brain and Glioma Cancermentioning
confidence: 99%
“…MRI is used before treatment and at the end of treatment or disease progression [295,296] and to assess neurological complications of cancer treatment [297]. PET/MRI is used in brain tumor grading and staging [298,299] as a diagnostic and therapeutic strategy for glioma [300] and for improved diagnostic and therapeutic assessment in pediatric, teenage, and young adult brain tumors [301]. 11 C-methyl-L-methionine (C-11-MET) PET/MRI was found to improve the diagnostic accuracy to differentiate treatment-related changes from true progression in recurrent glioma [302] and was useful for the assessment of isocitrate dehydrogenase (IDH) status [303].…”
Section: Brain and Glioma Cancermentioning
confidence: 99%
“…MRI provides excellent soft tissue contrast and spatial resolution without ionizing radiation, which has been widely used due to its relatively low cost and easy accessibility ( Mirzaei and Adeli, 2018 ). Meanwhile, PET imaging has been widely utilized in the diagnosis and management of cancer patients with relatively high sensitivity and quantitative-imaging ability ( Shankar et al, 2020 ; Overcast et al, 2021 ). However, these imaging examinations have showed a limited ability in the imaging of CNS-L mainly due to the special histopathological characteristics of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies (7,8,9,10,11) was performed a comparative study using MRI and Pet scan fused to MRI in brain tumor biopsy and found no significant difference in post-operative complications between these two groups. However, interestingly, the pathological diagnosis was higher in the MRI alone group.…”
Section: Svoa Neurologymentioning
confidence: 92%
“…In previous studies (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)13,14) it has been established that FD PET does not have sufficient sensitivity compared to other radiotracers; this is the case with choline, which allows better identification of the lesion with more sensitivity. In this case, methionine PET-CT radiotracer was used, allowing the metabolically active volume of the lesion to be accurately established.…”
Section: Svoa Neurologymentioning
confidence: 99%